Analisis Pengaruh CAR, NPF, DAR, DPK terhadap Pembiayaan Sektor Konstruksi pada Perbankan Syariah di Indonesia - Rr Dwi Waskita Ningsih; Radia Purbayati; Leni Nur Pratiwi (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
This research aims to determine the effect of Islamic banking internal factors include Capital Adequacy Ratio (CAR), Non-Performing Financing (NPF), Debt to Asset Ratio (DAR) and Third Party Funds (DPK) on the amount of financing disbursed to the construction sector in Islamic banking in Indonesia. 2015-2019. The research method used in this research is descriptive research with a quantitative approach using multiple linear regression analysis techniques. The data used are secondary data obtained from the Annual Financial Statements of Islamic Banking that are published by Otoritas Jasa Keuangan (OJK). The results of this research indicate that simultaneously the variables CAR, NPF, DAR and DPK have a significant effect on the financing of the construction sector. While partially, only NPF and DPK variables have a positive and significant effect on Construction Sector Financing.